A Web of Science based bibliometric reconnaissance of the Himalaya-Karakoram-Hindukush-Tibet region with focus on field sciences - Gautam, Pitambar (Journal of Nepal Geological Society, 2021)
A bibliometric survey of the Himalaya-Karakoram-Hindukush-Tibet (HKHT) region, the largest mountain system on Earth, for research publications recorded in the Web of Science (WOS) during 1901-2018 revealed 46,746 citable documents (articles, reviews, letters and notes) showing exponential growth mainly after 1980s. The HKHT publications that cover 244 WOS subject categories (SCs) have been used to determine the relative shares by HKHT units, countries, research organizations and publication sources. Nine WOS SCs related to “earth, environmental and agricultural sciences” exhibit highest shares (22.6% to 3.2% of the total) by the whole counting method. Further analysis of the 1994-2018 subset related to 4 broader disciplinary classes (Geosciences, Environmental Sciences & Technologies, Agricultural Sciences, and Ecological Sciences) attributed to “field sciences” with particular emphasis on the high impact (TOP10% globally by citation) documents enables to capture the most prolific, representative (both in space and time) and impactful research. This study identifies the prolific countries, institutions, journals, etc. characterizing the cross-disciplinary research transcending national boundaries and involving international teams. Science mapping of high impact publications (4,561 documents) using the co-occurrence of keywords restricted to noun phrases reveals six prominent clusters that reflect the prolific and high impact research themes in field science for the whole HKHT region: five of them related to earth and environmental sciences (climate change including monsoon regime, tectonic evolution of the Himalaya-Tibet orogen, India-Asia collision and associated crustal phenomena, activities on major thrusts, channel flows and inverted metamorphism), and one contrasting theme concerning the genetic diversity of plants mainly of medicinal values.